Emotional Induction Through Music: A comparison between European and Latin American music - López, Morena (2023)
Music can induce different emotional states on listener, a phenomenon termed Emotional Induction through Music (EIM). It has been mainly explained by intrinsic musical features, which lead to a classification of songs in two categories: arousing and relaxing. However, other aspects as contemporaneity and cultural proximity with music might influence EIM. This study aims to assess the EIM comparing music from different contexts and periods (European vs Latin American). Self-report measures (valence, arousal) and physiological parameters (heart rate variability [HRV] and skin conductance level [SCL]) were evaluated on an Argentinian sample (28 healthy volunteers, M = 27.45; SD = 1.31). After a three-minute physiological baseline, participants listened to musical fragments (arousing Latin American vs relaxing Latin American vs arousing European vs relaxing European) for three minutes each one. After each excerpt, participants rated their valence and arousal. Results showed that arousing Latin American music was rated as more positive and arousing than European music, and both were more positive and arousing than relaxing music. Physiologically, both arousing music elicited higher SCL than relaxing music. Moreover, arousing Latin American music presented an increase in low frequency component (HRV indexes) compared whit baseline and European arousing music. Thus, contemporaneity and cultural proximity could generate a differential effect and enhance EIM.